2016
DOI: 10.3847/0004-637x/823/1/55
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for the Photospheric Driving of Non-Potential Solar Coronal Magnetic Field Simulations

Abstract: In this paper, we develop a new technique for driving global non-potential simulations of the Sun's coronal magnetic field solely from sequences of radial magnetic maps of the solar photosphere. A primary challenge to driving such global simulations is that the required horizontal electric field cannot be uniquely determined from such maps. We show that an "inductive" electric field solution similar to that used by previous authors successfully reproduces specific features of the coronal field evolution in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…In future, the FRoDO code can be applied to higher resolution models of the coronal evolution that are currently under development (e.g., Weinzierl et al 2016). Similarly it could be applied to more hypothetical simulations of other stars (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In future, the FRoDO code can be applied to higher resolution models of the coronal evolution that are currently under development (e.g., Weinzierl et al 2016). Similarly it could be applied to more hypothetical simulations of other stars (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This particular date has been deliberately chosen since Weinzierl et al (2016) found a significant non-localized E ⊥0 caused by re-assimilation of a large active region (see their Figure 11). Here, we process the ADAPT data by (i) applying a multiplicative correction for flux balance; (ii) applying a spatial smoothing to the maps; and (iii) remapping to a 360 × 180 grid in φ and cos θ.…”
Section: Flux Imbalance In ∂ T B R Mapsmentioning
confidence: 99%
“…For example, Kazachenko et al (2014Kazachenko et al ( , 2015 have made this correction using observations of plasma velocities in active regions, and the resulting E ⊥ has been used to drive magneto-frictional simulations . On the other hand, Weinzierl et al (2016) have included the contribution to E ⊥ from a prescribed large-scale differential rotation in their global magneto-frictional simulations. In this paper, however, we will put this issue aside and focus only on the localization problem.…”
Section: Introductionmentioning
confidence: 99%
“…The new data are assimilated gradually over one day, so that there is no sudden change in the electric and magnetic fields. As in Weinzierl et al (2016), this is done by linearly interpolating the electric fields which are computed from the daily magnetograms as described in Section 3. The two active regions selected for this test are compact and well-separated from the surrounding magnetic fields.…”
Section: Datasetsmentioning
confidence: 99%